Development and Optimization of a New Chemoenzymatic Approach for the Synthesis of Peracetylated Lactosamine (Intermediate for the Synthesis of Pharmacologically Active Compounds) Monitored by RP- HPLC Method - Qais Ibrahim Abualassal; Khaldun Mohammad Al Azzam; Zead Helmi Abudayeh; Loay Khaled Hassouneh (Tabriz University of Medical Sciences, 2017)
Purpose: To describe a chemoenzymatic approach joining an enzymatic regioselective hydrolysis of peracetylated N-acetyl-α-D-glucosamine (A) with a mild controlled acyl relocation which resulted 2-acetamido-2 deoxy-1,3,6-tri-O-acetyl-α-D-glucopyranose (1B). Methods: Immobilization of lipase on decaoctyl (DSEOD) and octyl-agarose (OSCL) was carried out as reported by the work of Bastida et al. The newly developed RP-HPLC method for examining the enzymatic hydrolysis was carried out isocratically utilizing a HPLC system. Results: The new approach resulted the target compound (B) in 95% yield after purification utilizing flash column chromatography. Candida rugosa-lipase immobilized ondecaoctyl-sepabeads was the best catalyst in terms of activity and region-selectivity in the hydrolysis of substrate (A), delivering the deacetylation at C6 position (98% general yield). Also, a reversed-phase high-performance liquid-chromatographic (RP-HPLC) method for controlling the region-selective hydrolysis of peracetylated N-acetyl-α-D-glucosamine (A) with a mild monitored acyl movement which led to 2-acetamido-2-deoxy-1,3,6-tri-O-acetyl-α-D-glucopyranose (1B) has additionally been developed. The developed RP-HPLC method was utilized as fingerprints to follow the hydrolysis of substrate (A) and to determine its purity and additionally yield. Furthermore, the acquired compound (B) was further purified by flash chromatography. Compound (B) was further characterized utilizing 1HNMR and mass spectrometry. Conclusion: An efficient chemoenzymatic procedure to optimize the preparation of peracetylated lactosamine B containing acetyl ester as extraordinary protecting group is presented. Compound B is a significant intermediate for the synthesis of pharmacologically active compound (e.g. complex oligosaccharides for biochemical, biophysical, or biological examinations). Besides, reaction monitoring utilizing HPLC proposes more exact information than spectroscopic methods.